Italian causatives and the grammar of (in)direct causation - Donazzan, Marta (Revista Letras, 2017)
This paper tackles the issue of the relation between syntax and semantics in causative structures, and it concentrates on the empirical case offered by syntactic causative constructions in Italian. Italian exhibit two types of causative constructions (so-called faire-par and faire-infinitive constructions) that have been the subject of extensive inquiry in the literature. I argue that, in order to capture the semantic similarities and differences between the two types of syntactic causatives in Italian, it is necessary to relate their properties to the underlying causative structure that they express. This approach leads to the rejection of previous accounts that distinguish the two structural types based on the selectional properties of the first causative verb. An account in terms of Voice alternation is retained, and I present new empirical evidence for this approach, drawn from comparison with other causative constructions in Italian and from the discussion of the transitive/anticausative alternation in the infinitive clause.